Concealed penis: A review of multilevel classification and surgical reconstruction techniques - Bo‐yu Xiang; Jing‐xuan Peng; Xue‐jun Shang; Xiong‐bing Zu; Dong‐jie Li (BJUI Compass)
Abstract Concealed penis (CP), also known as hidden or buried penis, is an external genital deformity in which a normal‐sized penis is covered by skin, subcutaneous tissue or fat tissue in the prepubic area, leading to abnormal exposure. This condition has significant morbidity and a negative effect on certain aspects of the patient's quality of life, including but not limited to hygiene, micturition, self‐image and sexual function. Current classification systems for CP are heterogeneous, but most of these further classify CP based on their division into congenital concealed penis (CCP) and adult‐acquired buried penis (AABP). The aetiology and pathogenesis of this disease are understood to some extent, but the specific underlying mechanisms need further research. Although conservative treatment may be effective for some children with CCP, surgical intervention is still the main treatment for other children with CCP and AABP. There is no ‘gold standard’ surgical treatment for CP, but there are various surgical methods available; therefore, individualized surgical plans should be created after a comprehensive evaluation based on the classification and aetiology of CP patients.